Development of Virtual Reality Training Module in Beekeeping - Sevin, S; İnak, NK; Ekim, O; Yarsan, E (Journal of the Hellenic Veterinary Medical Society, 2025)
Virtual reality technologies have become powerful innovations in education, providing engaging and immersive environments that significantly improve learning experiences. Although VR applications are well-established in medical education, their use in veterinary sciences and entomology remains limited. Previous arthropod-focused VR projects provided insights into insect morphology and behavior but excluded honeybees. This study employs semi-immersive VR technology to develop a 3D virtual training system for beekeeping, addressing challenges such as fear, allergies, seasonal constraints, and the high costs of traditional training. The virtual environment includes three interactive modules: an introduction to beekeeping, equipment identification, and hive management practices. The modules integrate 3D-scanned models, informational content, and instructional videos to provide a comprehensive and flexible learning experience, with user-friendly navigation supported by hand controllers and guided cues. Implemented within the veterinary education program at Ankara University, the system serves both students and beekeepers, offering an innovative approach that complements theoretical instruction. Preliminary observations indicate that incorporating VR-based tools enhances engagement and understanding, providing a solution to overcome the limitations of conventional beekeeping education.